Landslide Hazard of Rock Slopes Around Shaqlawa City, Kurdistan Region, NE Iraq, with Modified Classification of Hazards on Roads and proposing remedial measurements - Al-Saadi, Saad Numan; Yousif, Luay Dawood (Sulaimani Journal for Pure and Applied Sciences, 2013)
The results of rock slopes analyses around Shaqlawa area showed that Landslide Possibility Index (LPI) values range between Low (LPI) for rock slopes of Tanjero, Kolosh and (marl and siltstone) of Gercus Formations, Moderate (LPI) for rock slopes of Shiranish, Gercus (sandstone and dolomitic limestone) and Pila Spi Formations, and High (LPI) for rock slopes of the dolomitic limestone of Pila Spi Formation at the gorge north of Shaqlawa city (at the west side of Shaqlawa - Harir main road). Two landslide hazard maps have been prepared for Shaqlawa area: A- The first Hazard map (based on LPI values) shows three hazard areas; (1) Area of Low Hazards (for Tanjero and Kolosh Formations). (2) Areas of Moderate Hazards (for Shiranish, Gercus and Pila Spi Formations) and (3) Area of High Hazard (for the dolomitic limestone beds of Pila Spi Formation) west of Shaqlawa - Harir main road. B- The second Hazard map (based on the effect of landslide on the roads), also shows three hazard areas but different from the first map. It shows; (1) Area of Very Low Hazard (it includes slopes of Tanjero, Kolosh and Gercus Formations) because of the wide distance between the failing slopes and the road, (2) Area of Moderate Hazard (in the slopes of Shiranish Formation) because of closeness from the road and poor protection works, and (3) Area of High Hazard (at Pila Spi dolomitic limestone slopes at the west side of Shaqlawa-Harir main road) due to its high slope angle and height, and closeness to the road in addition to poor protection works. A modification on the classification of landslide hazard on roads is suggested, and some measures of landslides treatment are suggested, for slope stabilization and road protection.
Keywords: Landslides; Shaqlawa area; Rock slopes; Hazard; Safin; Gird Sur; Shiranish